Pengaruh Thin Capitalization, Sales Growth, dan Transfer Pricing Terhadap Tax Avoidance - Adelia Noviani Umroatus Mafidah, Michel; Setyo Budiwitjaksono, Gideon (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research objective is to examine the influence of Thin Capitalization, Sales Growth, and Transfer Pricing on tax avoidance in property and real estate sector companies in 2019-2022. This research applies a quantitative research approach that utilizes secondary data obtained from financial reports and ongoing business reports. The research sample consisted of 89, the sample was selected using a purposive sampling technique, data was collected from 17 sample companies during the 4 year research period. Data analysis uses multiple regression analysis techniques to analyze the relationship between thin capitalization, sales growth, transfer pricing and tax avoidance. The research findings show that these factors have a considerable negative impact on tax avoidance. Therefore, if corporations apply a higher level of responsibility for thin capitalization, sales growth and transfer pricing in tax avoidance practices, this will effectively prevent potential tax avoidance from occurring.